Examining the simple and multiple relationship of parenting styles and early life trauma with narcissistic personality in university students - Ahmadi, Vahid; Nasrolahi, Abbas; Mirshekar, Sareh (Archives of Advances in Biosciences, 2015)
According to the high prevalence of narcissistic personality among normal populations, this study was conducted to found out the simple and multiple relationships of parenting styles and early traumas with narcissism personality in university students. The statistical society of current research included all students of Shahid Chamran University of Ahwaz. To perform this research, 314 students (159 female, 155 male) were selected by multistage randomly sampling method and complete narcissism personality inventory 16 items (Ames et al, 2006), parenting styles ( bum rind, 1990) and early trauma inventory. The data of questionnaire were analyzed by multiple regressions in stepwise and entry methods .The results of multiple regression analysis indicated that 66 percent narcissism personality variance in students was explained by parenting styles and traumas in early life. Also, early life trauma, avoidant and secure attachment emerged as the strongest predictors of narcissism personality in students. Given the role of parenting styles and early life trauma on the making of narcissistic personality in students, recommended that a set of training program will be used by specialist to prevent the narcissistic personality tendency.